2005
DOI: 10.1182/blood-2004-08-3253
|View full text |Cite
|
Sign up to set email alerts
|

Reduced plasma fibrinolytic potential is a risk factor for venous thrombosis

Abstract: The role of the fibrinolytic system in the development of deep vein thrombosis (DVT) is unclear. We determined the plasma fibrinolytic potential of patients enrolled in the Leiden Thrombophilia Study (LETS), a population-based casecontrol study on risk factors for DVT. Plasma fibrinolytic potential was determined in 421 patients and 469 control subjects by means of a tissue factorinduced and tissue-type plasminogen activator (tPA)-induced clot lysis assay. Using clot lysis times above the 70th, 80th, 90th, 95t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
219
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(247 citation statements)
references
References 30 publications
23
219
1
4
Order By: Relevance
“…We have recently shown in these same individuals that TAFI antigen levels and clot lysis times were only weakly associated (Lisman et al, 2005). The present study showed an increased risk of DVT in carriers of …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We have recently shown in these same individuals that TAFI antigen levels and clot lysis times were only weakly associated (Lisman et al, 2005). The present study showed an increased risk of DVT in carriers of …”
Section: Discussionsupporting
confidence: 59%
“…It was shown that clot lysis times were associated with both TAFI antigen and activity levels in a group of 20 healthy volunteers. However, recently we showed in a much larger group of healthy subjects (n ¼ 469), which is the control group of the study we report on here, that the association between the clot lysis time and TAFI antigen levels was, at most, very weak (0AE188 increase in clot lysis time (in min) per 1 U/dl increase in TAFI, after age-adjustment) (Lisman et al, 2005). In the total study population, 403 (43%) were men, 540 (57%) women and the mean age in patients and control subjects was 45AE0 years (range 15-69 years) and 44AE7 years (15-72 years), respectively.…”
Section: Discussionmentioning
confidence: 96%
“…by comparing the thrombin and reptilase-induced polymerisation profiles to identify the mechanisms of the defective conversion of fibrinogen to fibrin [30]. The clot lysis time has been widely used to assess the plasma fibrinolytic potential in a broad range of diseases [31][32][33][34][35]. In the setting of congenital dysfibrinogenaemia, fibrinogen variants with a well-identified thrombotic phenotype have been associated with hypofibrinolysis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma fibrinolytic potential of tissue factor induced clots, lysed by exogenous tissue plasminogen activator (tPA) [23][24][25] were determined for control plasma and plasma with different concentrations of 17β-estradiol (30,60,140, 220, 300 pg/ml and 1ng/ml) and progesterone (30, 60, …”
Section: Sample Preparation For Turbidimetric Analysismentioning
confidence: 99%